The Story of Baby Jesus - Retold by Kelly, Mary (London Usborne Publishing, 2011)
A colourfully illustrated retelling of the story of the Nativity for young readers
Include Color Illustration
Keywords: Nativity of Jesus Christ -- Jesus Christ -- Christmas